Plasticity of morphological traits in response to social conditions in a simultaneous hermaphrodite. Issue 1 (2nd January 2017) - Meconcelli, S.; Cannarsa, E.; Sella, G.
Abstract : According to sex allocation theory, hermaphrodites allocate a fixed amount of resources to their male and female functions, and the proportion of resources invested in each sex depends on the mating group size. Measures of trade-offs between male and female functions are usually made directly by estimating the number of gametes or the size of the gonads. In this study, we focused on the effect of social conditions (i.e. mating opportunities) on the expression of some morphological traits and on their plasticity in the protandrous simultaneously hermaphrodite Ophryotrocha diadema . We investigated whether in O. diadema the morphological traits, which are dimorphic in Ophryotrocha dioecious species – upper-jaw size, prostomium size, body size and number of rosette glands − are plastic when they respond to variations in social conditions and whether variations in these traits are associated with variations in male and/or female reproductive success. Plasticity of the traits was analysed during both the juvenile and the adult phases in order to check whether phenotypic plasticity is limited to the developmental phase or can be manifested throughout the whole lifespan of the animals. Our results showed that the number of rosette glands, the upper-jaw size and the prostomium size are traits that are plastic in O. diadema . Indeed, the number and size of these traits changed according to the variation of social conditions. However, we found no association between the plastic morphological traits and male or female reproductive success.